Pengaruh Keterampilan Awak Kapal dalam Penggunaan Peralatan Navigasi terhadap Keselamatan Pelayaran pada PT. Al Jazeera Shipping Co.W.L.L. - Putri Dwi Jayanti; Robertus Noreng (Sekolah Tinggi Manajemen Transportasi (STMT Malahayati Jakarta), 2023)
The purpose of this study was to determine how the influence of the skills of the crew in the use of navigation equipment on the safety of the shipping fleet at PT. AL JAZEERA SHIPPING.CO.W.L.L. The population in this study is the crew of a fleet of ships on PT. AL JAZEERA SHIPPING.CO.W.L.L, amounting to 21 people from 7 ships namely Sea Monarch, Sea Thunder, Al Aali 1, Al Faisal 1, Valian Eagle, Sea Dragon, Sea Majestic. The sample used was the entire crew of PT. AL JAZEERA SHIPPING.CO.W.L.L fleet, namely Sea Monarch, Sea Thunder, Al Aali 1, Al Faisal 1, Valian Eagle, Sea Dragon, Sea Majestic, amounting to 21 people with census techniques